Catalogue of the Georgian manuscripts, Holy Monastery of Iviron - Gippert, Jost (Holy Monastery of Iviron, 2022)
Prologue --Introduction.I.The collection of Georgian manuscripts in the Iviron Monastery ;II.Stocktaking the collection ;III.The structure of the catalogue ;IV.Acknowledgements --Description of the manuscripts --Indexes.I.Scribes, commissioners, binders etc. ;II.Authors ;III.Biblical figures ;IV.Saints, martyrs, anchorites ;V.Other persons mentioned ;VI.Place names ;VII.Manuscripts referred to ;VIII.Reference works ;IX.Liturgial terms ;X.Bibliography --Appendix A.Ruling schemes --Appendix B.Plates.